Asuhan Keperawatan pada Ny. N dengan Post Operasi Tumor Mammae Sinistra di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Nessy Meinika Putri; Ahmad Zakiudin; Sukirno Sukirno (STIKes Ibnu Sina Ajibarang, 2024)
Fibroadenoma of the breast (FAM) is a benign tumor that is painless, movable, has clear boundaries, and a rubbery texture. The incidence of cancer worldwide has increased, with the most common cancers reaching 24.5% and deaths reaching 15.5%, according to the WHO. In Indonesia, the prevalence reached 1.79% per 1,000 population in 2018, and in Central Java, it was 0.7% in 2019. Data from Dr. Soeselo Hospital in Tegal shows an annual increase of 2%, with prevalence reaching 1.9% in 2023, up from 1.7% in 2022. The aim of this research is to provide an overview of nursing care for patients who have undergone left breast tumor surgery. This research specifically focuses on the study involving diagnosis, determination of interventions, implementation, and evaluation. Using a case study design, a descriptive method was employed in this research. The writer narrates and explains the important events that occurred with the patient. Patients who have undergone surgery may experience pain after the operation, which could potentially lead to the risk of infection and a decline in knowledge. As a result, the nursing diagnosis that arises for the patient is acute pain. In the concept of pain, pain measurement is assessed using a numerical rating scale, and the patient's pain management involves relaxation breathing therapy and analgesics.